Rabacfosadine for relapsed canine B‐cell lymphoma: Efficacy and adverse event profiles of 2 different doses. (11th September 2017) - Saba, C. F.; Vickery, K. R.; Clifford, C. A.; Burgess, K. E.; Phillips, B.; Vail, D. M.; Wright, Z. M.; Morges, M. A.; Fan, T. M.; Thamm, D. H.
Abstract : Rabacfosadine (RAB), a novel double prodrug of the acyclic nucleotide phosphonate PMEG, preferentially targets neoplastic lymphocytes with reduced off target toxicity. Historical studies have suggested that every 21‐day dosing is effective with acceptable toxicity. The purpose of this study was to evaluate RAB's safety and efficacy at 2 different doses every 21 days in dogs with relapsed B‐cell lymphoma. Dogs that had failed 1 doxorubicin‐based chemotherapy protocol were eligible for inclusion in this prospective trial. Once enrolled, dogs were randomized to receive RAB at either 0.82 mg/kg or 1.0 mg/kg as a 30‐minute IV infusion every 21 days for up to 5 treatments. Response assessment and adverse event (AE) evaluation were performed every 21 days via VCOG criteria. Fifty dogs were enrolled, with 16 treated at 0.82 mg/kg and 34 treated at 1.0 mg/kg. The overall response rate was 74%, with 45% of dogs experiencing a complete response (CR). The median progression free intervals (PFIs) were 108 days, 172 days and 203 days for all dogs, all responders, and all CRs, respectively. Response rates and PFIs were similar in both treatment groups. The incidence of AEs, dose delays, dose reductions and withdrawals were not statistically different between the 2 groups. The AEs observed were similar to those previously reported and included hematologic, gastrointestinal, dermatologic and pulmonary AEs. One dog had grade 5 pulmonary fibrosis; otherwise, AEs resolved with supportive treatment. Rabacfosadine is a generally well tolerated, effective chemotherapy option for dogs with relapsed B‐cell lymphoma.